2021
DOI: 10.1186/s12891-021-04471-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between femoral neck and LS-BMD with LS-TBS in T2DM patients: a case control study

Abstract: Background Despite having higher bone mineral density (BMD) values, type 2 diabetes mellitus (T2DM) patients are at increased risk of fracture. Trabecular bone score (TBS) obtained by evaluating bone microarchitecture might be a more accurate factor for determining bone strength in T2DM patients. In this study, we aimed at investigating the mean values of lumbar spine (LS) TBS, LS-BMD, and femoral neck BMD in T2DM patients and controls, as well as the ability of LS-TBS and BMD in distinguishing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…8 DXA is also used for the diagnosis of osteoporosis. 16 Femoral neck and lumbar spine BMDs were found to be significantly higher in total population and males with T2DM, 17 In clinical practice, the risk of fracture is particularly overlooked in diabetic patients with normal BMD, especially in male patients with obesity. Analyzing fracture risk and BMD alone lacks sensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…8 DXA is also used for the diagnosis of osteoporosis. 16 Femoral neck and lumbar spine BMDs were found to be significantly higher in total population and males with T2DM, 17 In clinical practice, the risk of fracture is particularly overlooked in diabetic patients with normal BMD, especially in male patients with obesity. Analyzing fracture risk and BMD alone lacks sensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…The bone deleterious effects of insulinopenia are very-well seen in type 1 diabetes mellitus (T1D), where low bone mass accrual is seen after disease onset [ 28 ]. T2M patients are reported to have increased BMD [ 29 ], probably due to increased BMI, which is a protective factor against osteoporosis in all populations due to the mechanical loading [ 30 ]. Our group also found BMI to be a positive independent predictor in T2M [ 31 ].…”
Section: Preptin Insulin Resistance and Bone Metabolismmentioning
confidence: 99%
“…Hyperinsulinism secondary to insulin resistance may contribute to this finding. However, cortical bone microarchitecture is altered in T2M patients [ 32 ], which exhibit reduced trabecular bone score despite increased BMD [ 29 ]. In advanced disease, microvascular damage, insulinopenia and visceral adiposity negatively impact bone mass and turnover [ 26 ].…”
Section: Preptin Insulin Resistance and Bone Metabolismmentioning
confidence: 99%
“…women) and without T2D (n ¼ 484, age ¼ 58.5 AE 13.0 years; 87.6% women), although subjects with T2D showed significantly lower TBS compared to controls in the total population and in women, TBS showed similar discriminative capabilities than lumbar spine and femoral neck aBMD in differentiating subjects with and without T2D in the total population and in women (area under the curve [AUC] $ ¼ 0.64) [12].…”
Section: Key Pointsmentioning
confidence: 99%
“…The authors of the study also reported that differences in TBS between subjects with and without T2D were not independent of lumbar spine aBMD in men and women regardless of the degree of T2D control, except between well controlled T2D and non-T2D women (higher TBS in well controlled T2D women). Furthermore, in a recent cross-sectional study by Delbari et al between subjects with ( n = 150, age = 62.5 ± 10.2 years; 86% women) and without T2D ( n = 484, age = 58.5 ± 13.0 years; 87.6% women), although subjects with T2D showed significantly lower TBS compared to controls in the total population and in women, TBS showed similar discriminative capabilities than lumbar spine and femoral neck aBMD in differentiating subjects with and without T2D in the total population and in women (area under the curve [AUC] ∼ = 0.64) [12].…”
Section: Dual-energy X-ray Absorptiometrymentioning
confidence: 99%